Whitman's "the Million Dead, Too, Summ'd Up" in an age of endless war. Issue 1 (2nd January 2020) - Wilson, Joel Eric
Abstract: Walt Whitman's "The Million Dead, Too, Summ'd Up" is often read as an exaggeration of the casualties of the Civil War. Yet, by understanding Whitman's words through the lens of PTSD, readers may see that the "unknown" Whitman mentions may not only include the unidentified remains of soldiers buried in mass graves. Rather, in line with Whitman's accounts in Specimen Days, November Boroughs, and his poem, "The Artilleryman's Vision, " the "unknown" may be understood as a reference, at least in part, to the thousands, likely including Whitman himself, who were changed by PTSD in ways not fully understood during this time. The implications of this reading, then, make "The Million Dead, Too, Summ'd Up" an important part of Whitman's body of works considering the military activities in which American servicepeople continue to engage.